2013
DOI: 10.1186/1750-1326-8-43
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock factor 1 over-expression protects against exposure of hydrophobic residues on mutant SOD1 and early mortality in a mouse model of amyotrophic lateral sclerosis

Abstract: BackgroundMutations in the Cu/Zn superoxide dismutase gene (SOD1) are responsible for 20% of familial forms of amyotrophic lateral sclerosis (ALS), and mutant SOD1 has been shown to have increased surface hydrophobicity in vitro. Mutant SOD1 may adopt a complex array of conformations with varying toxicity in vivo. We have used a novel florescence-based proteomic assay using 4,4’-bis-1-anilinonaphthalene-8-sulfonate (bisANS) to assess the surface hydrophobicity, and thereby distinguish between different conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 78 publications
1
40
0
Order By: Relevance
“…We have previously shown that overexpression of heat shock factor 1 (HSF1), the master transcription factor for HSPs, has protective effects in ALS and AD mouse models (Lin et al, ; Pierce et al, ). HSF1 increased the solubility of mutant SOD1 concomitantly with delayed disease onset (Lin et al, ) and ameliorated AD‐like cognitive impairment (Pierce et al, ). Other studies have shown that multiple HSPs are responsible for TDP‐43 homeostasis and metabolism.…”
mentioning
confidence: 99%
“…We have previously shown that overexpression of heat shock factor 1 (HSF1), the master transcription factor for HSPs, has protective effects in ALS and AD mouse models (Lin et al, ; Pierce et al, ). HSF1 increased the solubility of mutant SOD1 concomitantly with delayed disease onset (Lin et al, ) and ameliorated AD‐like cognitive impairment (Pierce et al, ). Other studies have shown that multiple HSPs are responsible for TDP‐43 homeostasis and metabolism.…”
mentioning
confidence: 99%
“…small HSP HSP27 (HSPB1) AD/ Aβ Reduced Aβ aggregation in vitro and toxicity on cells [98] and in mice [99]; alters tau dynamics in mice [100]; reduced polyQ aggregation and toxicity in cells [101] and by viral delivery in rats [102] but not transgenic mice [103]; reduced α-synuclein fibril AD/Tau HD/Htt AD deficits in mice [120]; polyQ in mice [121]; mutant SOD1 in mice [122].…”
Section: Chaperone Family Chaperone Disease/protein(s) Commentsmentioning
confidence: 99%
“…Induction of HSP40/70 in spinal cords of G93A SOD1 mice, by 2–3 fold, has been demonstrated by transgenic over‐expression of HSF1, using a transgene vector that expresses in both neurons and astrocytes (Lin et al . ). This report did not provide histologic evaluation of which cells responded to the added HSF1 expression.…”
mentioning
confidence: 97%
“…Although this study reported that the age at which mice that were bigenic for the G93A mutant SOD1 and HSF1 first developed symptoms was later than that of mice that express the G93A mutant alone, on the whole, the average age to paralysis for bigenic mice was not statistically different from that of mice expressing SOD1‐G93A alone (Lin et al . ). Collectively, these studies provide a mixed view of the potential efficacy of inducible HSPs in ameliorating the phenotypes caused by expression of mutant SOD1.…”
mentioning
confidence: 97%
See 1 more Smart Citation